Ordem e progresso: a imprensa da Zona da Mata Mineira na década de 1920 - Carvalho, Daniela Corrêa e Castro de (2007)
The Republic’s slogan simplifies how the newspapers of Zona da Mata Mineira, O Operário, from Muriaé, and Jornal de Viçosa, from Viçosa, addressed 1920 decade events. This work begins with a review of the Republic deployment until the end of 1920 decade, and based on these events, it analyzes, following Michel Foucault micropowers’ conception, the newspapers published between 1920-1929 to investigate how they described the society that they were in, from the national to the local events, such as the Tenentismo, elections, and daily life of small cities from Minas Gerais, in particular the richest area of the state on that time, the Zona da Mata.